2020
DOI: 10.21101/cejph.a6211
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing, subjective perception, demographic factors, and prevalence of burnout syndrome in nurses

Abstract: Objectives: The aim of the study was to assess the prevalence of burnout syndrome and mobbing, to determine their mutual relationship, and to identify predictors related to the probability of occurrence of burnout syndrome in general nurses working in hospitals. Methods: The work is designed as a cross-sectional study. The research took place in 2018 and the sample included 250 general nurses. Statistical evaluation was performed by means of descriptive statistics, Spearman's correlation coefficient, and logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
1
3
0
1
Order By: Relevance
“…Our study showed that bullying in the workplace is significantly concerned with intensive care nurses' burnout. Results of previous studies with different participants such as school principals 42 and general nurses 43 support this finding.…”
Section: The Relation Between Bullying and Burnoutsupporting
confidence: 69%
See 1 more Smart Citation
“…Our study showed that bullying in the workplace is significantly concerned with intensive care nurses' burnout. Results of previous studies with different participants such as school principals 42 and general nurses 43 support this finding.…”
Section: The Relation Between Bullying and Burnoutsupporting
confidence: 69%
“…45 Eventually, this cycle leads to complete depletion of resources (burnout). 45 It has been shown that bullying in the workplace through undermining and threatening the victim's self-esteem can lead to a flare-up of stress 43 and trigger the cycle of resource loss, stress and burnout.…”
Section: The Relation Between Bullying and Burnoutmentioning
confidence: 99%
“…Similarly, nurses ranked first place as plaintiffs in mobbing lawsuits according to the findings of this study. It has been stated in many studies that nurses are one of the occupational groups at risk in terms of mobbing in the workplace (Cakirpaloglu et al, 2017; Einarsen et al, 1998; Gómez‐Urquiza et al, 2017; Milutinović et al, 2009; Vévodová et al, 2020). These research findings showed that nurses all over the world are victims of physical, emotional, and verbal violence due to the nature of their work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the mass potentially negative impacts of burnout on both the health and quality of patient care, the driving factors of the rising burnout issue had been paid more attention. Based on previous literature, several demographic and job characteristics were suggested to be associated with burnout among medical staffs, such as age ( 25 ), sex ( 25 ), job tenure, work hours education level ( 26 ), professional titles ( 27 ), and so on. However, overall evidence on demographic and job factors of burnout among nurses was inconclusive ( 28 ) in different space-time settings and deserves a wide range of attention.…”
Section: Introductionmentioning
confidence: 99%